Knowledge and awareness of tuberculosis prevention efforts: literature review - Andi Muthiyah A AM (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Tuberculosis is a major trigger for morbidity and mortality worldwide. TB infection can occur due to pathogenic germs, namely mycobacterium tuberculosis infection. The literature review aims to obtain an overview of knowledge and awareness of public attitudes towards efforts to prevent tuberculosis infection. The research method used is a literature review study. Researchers analyze the research data obtained and then take the essence of various relevant research data. Based on information sources obtained from 10 articles from Indonesian and international journals in the 2011–2023-time frame. From several studies that have been conducted before, it shows that there is a relationship between the level of education that affects public knowledge in taking a tuberculosis prevention stance. In addition, there are also other factors that cause negative attitudes towards tuberculosis prevention, these factors are tuberculosis patients rarely carry out routine control every 6 months, use dust masks, sputum examinations, and the influence of emotional factors from sufferers. It was concluded that there is a relationship between the level of public knowledge on attitude making and tuberculosis prevention efforts. The higher the level of community education in line with the higher the level of community knowledge in prevention efforts